Computer vision for Pokémon Battles: A YOLO and Tesseract-Based System for Automated Recognition and Gameplay Analysis - Lladó, Miguel R. (2025)
Pokémon Double Battles present a complex decision-making environment that has traditionally relied on manual data analysis. This paper introduces an automated system leveraging computer vision and deep learning to extract structured gameplay data from battle footage. Our approach integrates You Only Look Once (YOLO) for Pokémon sprite recognition along with Tesseract-based optical character recognition (OCR) for extracting move and status text. The study introduces a custom-built image dataset generated through the augmentation of publicly available Pokémon sprites, which is then used to train a YOLO model for sprite recognition. The system was tested across multiple controlled and real-world gameplay scenarios, achieving high accuracy in Pokémon recognition and action tracking. Additionally, a JSON-based gameplay notation system is proposed to structure battle sequences, thus improving analysis and strategic review. The results demonstrate the feasibility of AI-driven gameplay analysis, with potential applications for competitive players, game analysts, and developers. Given its exploratory nature, this study focuses on technical feasibility rather than statistical generalisation. Future work includes expanding the dataset, improving OCR performance, and enabling real-time processing to support broader practical use.